The beneficial effects of green tea on sleep deprivation-induced cognitive deficits in rats: the involvement of hippocampal antioxidant defense - Fatemeh Forouzanfar (Elsevier, 2021)
Background: The weight of evidence suggests that sleep is essential for the processes of memory consolidation and sleep deprivation (SD) impairs the retention of long-term memory in both humans and experimental animals, which is associated with oxidative stress damage within the brain. Green tea polyphenols have revealed carcinogenic, antioxidant, anti-, and anti-mutagenic properties. We aimed to investigate the possible protective effect of green tea extract (GTE) and its main active catechin, epigallocatechin-3-gallate (EGCG), on post-training total sleep deprivation (TSD) -induced spatial memory deficits and oxidative stress profile in the hippocampus of the rat. Methods: Male rats were treated with saline, GTE (100 and 200 mg/kg/day), and EGCG (50 mg/kg/day) intraperitoneally for 21 days and then trained in Morris water maze (MWM) in a single day protocol. Immediately after the end of MWM training, animals were sleep deprived for 6 h by the gentle handling method, and then evaluated for spatial memory. Hippocampal levels of malondialdehyde, (MDA), and thiol was assessed as oxidant and antioxidant markers. Results: Spatial memory was impaired in the TSD group and GTE at the dose of 200 mg/kg/day as well as EGCG at the dose of 50 mg/kg/day could reverse the impairment to the saline-treated levels. Despite the unchanged MDA levels, hippocampal total thiol was significantly decreased after TSD and EGCG increased it to the basal levels. Conclusion: In conclusion, green tea and its main catechin, EGCG, could prevent memory impairments during 6 h of TSD; probably through normalizing the antioxidant thiol defense system which was impaired during TSD.